A DIGITAL TO ANALOG VOLTAGE CONVERTER EXPERIMENT FOR MICROCONTROLLER COURSE - INCELİ, Seyma; YUKSEKKAYA, Mehmet (The Eurasia Proceedings of Educational and Social Sciences, 2017)
Teaching modules and programming of a microcontroller through experiments is a very efficient method. Microcontroller programming usually also requires practical electronics knowledge. Variable analog voltage outputs are usually not available in common microcontrollers, but this type of signal is required for many applications. This experiment is proposed to teach digital to analog voltage conversion (DAC) using pulse width modulation (PWM) by a microcontroller. In the experimental procedure students should generate the PWM signal, develop digital to analog voltage regulator circuit, design a ripple filter, review the experimental results and answer the questions. Students are expected to observe and interpret the code writing, the digital to analog converter and ripple filter effect. This paper describes, the experimental procedure, the materials and methods used in the experiment and the main theoretical concepts, and determine the evaluation methods for the benefits of the experiment. This experiment will be applied to biomedical engineering undergraduates. Their performances will be evaluated through surrey questions and their grades.